2018
DOI: 10.1371/journal.pone.0200540
|View full text |Cite
|
Sign up to set email alerts
|

MARCH1-mediated ubiquitination of MHC II impacts the MHC I antigen presentation pathway

Abstract: Major histocompatibility complex class II (MHC II) expression and turn-over are regulated via its ubiquitination by the membrane associated RING-CH 1 (MARCH1) E3 ligase. Unexpectedly, we show that MHC II ubiquitination also impacts MHC I. Lack of MARCH1 in B cells and dendritic cells (DCs) resulted in a significant reduction in surface MHC I expression. This decrease was not directly caused by changes in MARCH1 ubiquitination of MHC I but indirectly by altered MHC II trafficking in the absence of its ubiquitin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 44 publications
7
33
0
Order By: Relevance
“…In contrast, SteD clearly increased the amounts of di-ubiquitinated mMHCII, and MARCH8 was not required for this ( Figure S1 C). We confirmed that surface levels of MHCII in a March1 −/− mouse-derived MutuDC cell line were higher than in wild-type cells ( Wilson et al., 2018 ) ( Figure S1 D). In mouse cells, it is not possible to discriminate between immature and mature MHCII molecules, so measurements of MHCII in these cells reflect both forms.…”
Section: Resultssupporting
confidence: 72%
“…In contrast, SteD clearly increased the amounts of di-ubiquitinated mMHCII, and MARCH8 was not required for this ( Figure S1 C). We confirmed that surface levels of MHCII in a March1 −/− mouse-derived MutuDC cell line were higher than in wild-type cells ( Wilson et al., 2018 ) ( Figure S1 D). In mouse cells, it is not possible to discriminate between immature and mature MHCII molecules, so measurements of MHCII in these cells reflect both forms.…”
Section: Resultssupporting
confidence: 72%
“…Further, another study confirmed that the immunosuppressive effect of IL‐10 on antigen presentation is mediated through induced expression of MARCH1 (Galbas et al, 2012). Of note, MARCH1 can suppress DC maturation, decreasing the expression of costimulatory molecules and MHC class II (MHC‐II) by ubiquitination of CD86 and MHC‐II β‐chains, respectively (Wilson et al, 2018). Therefore, MARCH1‐mediated ubiquitination of MHC‐II molecules has a regulatory effect on the immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 11 members of the MARCH family, some play important roles in immune regulation, such as endoplasmic reticulum degradation, protein‐energy control, and membrane transport (Lin et al, 2019; Nakamura, 2011). MARCH1, expressed by antigen‐presenting cells (APCs), dendritic cells (DCs), and B cells in lymphoid tissues (e.g., the spleen), participates in the regulation of antigen presentation via the ubiquitination of major histocompatibility complex (MHC)‐II and CD86 (Corcoran et al, 2011; Wilson et al, 2018). Many studies have reported the role of MARCH1 in the immune system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On BTA6, the MARCH1 gene was associated with semen production traits in Chinese Holstein bulls (Liu et al, ). Also, this gene is associated with the major histocompatibility complex I (MHC I), acting in the process of recognition of antigen presentation (Wilson et al, ), and was found in a candidate region affecting female sexual precocity (Table ). On BTA7, PBX4 gene is located in mouse testis and participates of spermatogenesis (Wagner, Mincheva, Korn, Lichter, & Pöpperl, ).…”
Section: Discussionmentioning
confidence: 99%